First description of co-occurrence of 49,XXXXY and X-linked Cornelia de Lange syndrome: case report - Al-Rashdi, Sumaiya; Ekstrom, Lori; Collins, Aedin; Schulz, Heidi L.; Dinwiddie, April; Samango-Sprouse, Carole; Olaya, Margaret; Moser, Elizabeth; Green, Andrew J. (Frontiers in Endocrinology, 2025)
49,XXXXY is a rare sex chromosome aneuploidy with an estimated incidence of 1 in 85,000–100,000 newborn males. Individuals with this syndrome exhibit variable clinical manifestations, typically including developmental delay, intellectual deficits, hypogonadism, and distinctive facial features such as ocular hypertelorism, epicanthic folds, a flat nasal bridge, prognathism, folded-over ears, and a short neck. Unlike patients with Klinefelter syndrome, they are often short in stature. Cornelia de Lange syndrome (CdLS) is an unrelated rare disorder with an incidence of 1 in 10,000–30,000 live births, affecting both sexes. CdLS shares overlapping features with 49,XXXXY, including intellectual deficits and hypogonadism. However, it also presents with unique facial characteristics, such as synophrys, thick or highly arched eyebrows, low-set ears, upturned nasal tips, long eyelashes, and microcephaly. CdLS is a clinically and genetically heterogeneous condition, with severe cases involving congenital malformations including limb anomalies, and milder cases showing only subtle facial dysmorphism. Both syndromes may also involve cardiac and renal anomalies. We report the first documented concurrence of 49,XXXXY and X-linked CdLS, emphasizing the challenges in diagnosis and the phenotypic overlap between these two rare syndromes, and propose a theoretical mechanism for the co-occurrence.